Comparative evaluation of loop-mediated isothermal amplification (LAMP) assay, GeneXpert MTB/Rif and multiplex PCR for the diagnosis of tubercular lymphadenitis in HIV-infected patients of North India. (December 2019) - Baikunje, N.; Behera, D.; Rajwanshi, A.; Sharma, M.; Sharma, A.; Sharma, K.
Abstract: Background: Tubercular lymphadenitis (TBLA) is one of the most common extrapulmonary manifestations of tuberculosis in patients with HIV. With several other pathological conditions presenting as lymphadenitis and lack of consensus regarding a gold standard test, the diagnosis of TBLA remains a challenge for the clinician. Objectives: and design: In this study, we have assessed the potential of loop-mediated isothermal amplification (LAMP) test for the diagnosis of TBLA in HIV-infected patients. The study group included samples collected by fine needle aspiration (FNAC) of lymph nodes from 24 HIV-infected patients with TBLA. A composite reference standard was used to identify cases of TBLA based on clinical suspicion, results of cytology, AFB smear, MGIT culture, GeneXpert MTB/RIF, multiplex polymerase chain reaction (MPCR) and subsequently clinical response to antitubercular therapy. These tests were also carried out in 26 control samples of lymph node FNAC from HIV-infected patients with non-tubercular lymphadenitis. Results: LAMP assay was positive in 19/24 TBLA cases and yielded a sensitivity of 79.17% with 100% specificity. Cytology was suggestive in 18/24 (75%) TBLA cases. GeneXpert MTB/RIF assay correctly identified 16/24 TBLA cases, but the test did show one false positive result reducing its specificity. MPCR had the highest sensitivity of 91.67% as it correctly identified 22/24 cases and showed no false positive result. Conclusion: The current study highlights the potential of LAMP test for the specific diagnosis of tubercular lymphadenitis in FNAC samples from HIV-infected patients, especially when cytology is either non-conclusive or non-available. Though MPCR had a higher sensitivity than LAMP assay, the added advantages of low cost, minimal technical expertise and simplicity of procedure make LAMP assay a suitable diagnostic test in resource-limited settings. Highlights: Diagnosing tubercular lymphadenitis (TBLA) in HIV patients is challenging. Need for simple, accurate, inexpensive test. GeneXpert has low sensitivity and may give false positive result. LAMP assay: a suitable alternative for resource-limited countries.